Application of Good's buffers to pH imaging using hyperpolarized 13C MRI1. Issue 74 (25th September 2015) - Flavell, Robert R.; von Morze, Cornelius; Blecha, Joseph E.; Korenchan, David E.; Van Criekinge, Mark; Sriram, Renuka; Gordon, Jeremy W.; Chen, Hsin-Yu; Subramaniam, Sukumar; Bok, Robert A.; Wang, Zhen J.; Vigneron, Daniel B.; et al.
<x xml:space="preserve">Abstract</x> ACES, one of Good's buffers, was applied to pH imaging with hyperpolarized 13C spectroscopy.